MAKNA KATA AULIYA’ DALAM PERSPEKTIF PENDIDIKAN ISLAM - Liddini, Laily; Prayoga, Unggul; Luthfia, Chaula (Al Ulya: Jurnal Pendidikan Islam, 2022)
This article is an offer to understand the meaning of Auliya and its derivation in the Qur'an. Namely as a way to understand the meaning of auliya' according to Mufassir M. Quraish Shihab who is the main reference in interpretation in Indonesia. In this article, the author uses a qualitative research method, which is a method used to explore the meaning contained in it. In the research, the writer refers to the interpretation of Prof. M. Quraish Shihab to explore the meaning of auliya 'in QS. al-Maidah verse 51 and its derivation. The purpose of this paper is to reveal the meaning of the word auliya 'in QS. al-Maidah verse 51 which can be understood that auliya 'is a polysemy word which has the meaning of leader and lover. From the results of this study that M. Quraish Shihab's interpretation of the word auliya 'in the sense of love (mawaddah). Islamic education has an important position in human life, shaping humanity in accordance with the laws and values of Islamic teachings. The meaning of the word auliya which means thefabric of love (Mawaddahh) is very important in developing students so that they can understand and practice the results of Islamic education as a whole so that they have maturity in faith and piety, in accordance with the provisions contained in the Qur'an and al-Hadith